Dietary intake, physical activity and risk for chronic diseases of lifestyle among employees at a South African open-cast diamond mine - Stadler, Karen (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MNutr (Human Nutrition))--University of Stellenbosch, 2006.